2022
DOI: 10.1177/0271678x221134384
|View full text |Cite
|
Sign up to set email alerts
|

Association between susceptibility value and cerebral blood flow in the bilateral putamen in patients undergoing hemodialysis

Abstract: Hemodialysis (HD) is the most regularly applied replacement therapy for end-stage renal disease, but it may result in brain injuries. The correlation between cerebral blood flow (CBF) alteration and iron deposition has not been investigated in patients undergoing HD. Ferritin level may be a dominant factor in CBF and iron deposition change. We hypothesize that ferritin level might be the key mediator between iron deposition and CBF alteration. The correlation in the putamen was estimated between the susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…In our previous study, hemodialysis patients showed changed global susceptibility values in the primary motor cortex, salience network, and limbic system. 38 In this study, higher susceptibility values in the bilateral putamen and caudate and lower susceptibility values in the bilateral hippocampus, thalamus, and fusiform gyrus were found in the CKD 5ND group compared with the HC group. The pattern of iron deposition in patients with CKD 5ND was completely different from that in patients undergoing maintenance hemodialysis.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…In our previous study, hemodialysis patients showed changed global susceptibility values in the primary motor cortex, salience network, and limbic system. 38 In this study, higher susceptibility values in the bilateral putamen and caudate and lower susceptibility values in the bilateral hippocampus, thalamus, and fusiform gyrus were found in the CKD 5ND group compared with the HC group. The pattern of iron deposition in patients with CKD 5ND was completely different from that in patients undergoing maintenance hemodialysis.…”
Section: Discussionsupporting
confidence: 46%
“…The pattern of iron deposition in patients with CKD 5ND was completely different from that in patients undergoing maintenance hemodialysis. 38 Because patients with ESKD are affected by renal anemia, iron agents and recombinant human erythropoietin are frequently used to promote erythropoiesis and maintain normal target levels of hematocrit and hemoglobin. This may lead to systemic iron overload and subsequent iron transport into the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations